Participation in Decision Making and Use of Contraception (Modern or Traditional) and Unmet Need in Rural Urban of Yogyakarta - Wiwik Puji Mulyani; Tuffahati Nadhifa Srihadini; Sulistiawan Fajar Nugroho; Amanda Irbah; Sri Rum Giyarsih (Universitas Pendidikan Ganesha, 2024)
The Province of Yogyakarta Special Region is one of the provinces with fairly good contraceptive program achievement. This can be seen from the 2017 IDHS data, which shows that the DIY Province has a contraceptive prevalence among married women (age 17-49 years) of 76%. However, there are still many married women in DIY who prefer to use traditional contraception over modern contraception. Many things certainly influence this decision. One possible thing related to this is gender, especially women's independence. In addition, DIY's unmet need based on the 2017 IDHS is 6.2 percent. The objectives to be achieved are to analyze the use of modern and traditional contraception according to women's participation in household decision-making in rural and urban areas and analyze unmet needs according to women's participation in household decision-making in rural and urban areas. This research is a quantitative descriptive study using the 2017 IDHS data and emphasizes the analysis of spatial variations. Women who participate or do not participate in decision-making show a higher percentage of using contraception than those not using contraception. The percentage of use of contraceptives in urban areas is more significant than in rural areas. The use of modern methods of contraception shows a higher percentage in urban areas, whether involving women's participation or not. Married women aged 15-49 who participate in decision-making in the Special Region of Yogyakarta are dominated by the unmet need for birth control. The implication is that it is necessary to maintain low fertility values through contraception that has been embedded in both rural and urban areas and gender status, as well as understanding in depth how to avoid unwanted pregnancies.